Doing ethnomethodological ethnography. Moving between autoethnography and the phenomenon in “hybrid studies” of taiji, ballet, and yoga - Eisenmann, Clemens; Mitchell, Robert (Qualitative research : QR, 2024)
Based on the authors’ ethnographies in the fields of taiji, ballet, and yoga, this article outlines and reflects the theoretical and empirical scope of what we mean by “ethnomethodological ethnography.” Ethnomethodology and Conversation Analysis (EM/CA) have been juxtaposed and pit against various forms of ethnography and vice versa—for example, by criticizing various theoretical underpinnings of ethnographies, viewing EM/CA as a very limited micro-sociological research method, or by critiquing (auto-)ethnography as egocentric, self-absorbed, and ill-equipped to account for the detail and sequential organization of natural occurring actions and circumstances. Contrary to such deliberations, we highlight their common interest in putting empirical social phenomena first. In getting access to and describing what social phenomena consist of, members’ competencies and detailed analysis of recorded data mutually elaborate each other. In this sense, they are potentially not only mutually inclusive but, as we shall argue, the entire field of EM/CA studies depends to some degree on actually doing ethnography. Based on our own ethnographic research, we will then zoom in on the case of taiji practice to highlight the relevance of autoethnography and evaluate how ethnographic reflections of self and body constitute and may foster “uniquely adequate” qualitative research. Ultimately, the aim is to explicate how EM/CA research policies differ from textbook oriented instructions and are better considered as praxeological respecifications of doing ethnomethodological ethnography in particular cases.